Sacred history vs. secular history: historiographical controvercies over prie history and history of ancient israelites - Pažėraitė, Aušra (Religija ir kultūra, 2007)
In this article I’ve made an overview of modern scholarly maximalistic vs. minimalistic discussion concerning History of Ancient Israelites. Namely, some points of development of modern Continental and American Biblical scholarship (Wellhausen, Noth, Allbright, etc.), and New scholarship which emerged in early eight decade of 20th c. (Th. Thompson, N.P. Lemche, and others). In my article I argue, that this New scholarship, in its attempt to divorce scholarly researches of Ancient History of Israelites from reading the Bible as the source of that history, brings the Bible back to traditional rabbinical and Christian reading of it as a source of spiritual and theological meaning rather than historical, and that traditional rabbinical exegetical approach to Tanakh was a-historical as well, that is, divorced from historical perspective in the modern sense of History, though gives interpretations of History, as does authors of Tanakh, too. This divorce actually opens perspectives to serious academic researches of the History of Ancient Israelites as well as unbinds the reading of Bible from violence of History, from literal reading which often leads to violence, to renew the reading from various rabbinical, Christian theological, mystical and other hermeneutic perspectives and methods, which interpret that History and gives meaning to it.
Keywords: Bible; ancient israelites; maximalistes; minimalistes; historicity